2020
DOI: 10.3389/fnins.2020.00730
|View full text |Cite
|
Sign up to set email alerts
|

Bergapten Improves Scopolamine-Induced Memory Impairment in Mice via Cholinergic and Antioxidative Mechanisms

Abstract: Bergapten is a furanocoumarin naturally occurring in the Apiaceae family and it is a well-known photosensitizing agent used in photochemotherapy. In this study, we investigated the influence of bergapten on cognitive function and mechanism underlying these effects in scopolamine-induced memory impairment in male Swiss mice. The passive avoidance test was used to evaluate the efficiency of memory acquisition and consolidation. The results demonstrated that both sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Biochemical data suggested that scoparone (5 and 12.5 mg/kg) inhibits the increase of AChE, but no BChE was observed upon scopolamine (1 mg/kg) injection. This is in line with our previous studies where the furanocoumarins xanthotoxin and bergapten diminished the level of AChE and increased the antioxidative capacity in the hippocampus and prefrontal cortex in the scopolamine model of dementia in mice 14 , 38 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Biochemical data suggested that scoparone (5 and 12.5 mg/kg) inhibits the increase of AChE, but no BChE was observed upon scopolamine (1 mg/kg) injection. This is in line with our previous studies where the furanocoumarins xanthotoxin and bergapten diminished the level of AChE and increased the antioxidative capacity in the hippocampus and prefrontal cortex in the scopolamine model of dementia in mice 14 , 38 .…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the scopolamine model of dementia relates to cholinergic processes underlying memory functioning. Scopolamine was also found to cause lipid peroxidation by triggering free radical production, especially malondialdehyde (MDA) in combination with a decrease of antioxidative enzymes in the brain 38 . In our study, the scopolamine-induced memory impairments were attenuated by scoparone, indicating that scoparone treatment may also alter cholinergic neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…This journal is © The Royal Society of Chemistry 2022 increase the activities of AChE. 51,52 Older reports have shown that scopolamine may inhibit AChE activity. 53 However, in our study, SCOP enhanced the AChE activity in a significant manner.…”
Section: Food and Function Papermentioning
confidence: 99%
“…People with AD are commonly treated with procognitive medicines. However, the hepatotoxicity and the side effects arising from the activation of the cholinergic system limit the use of AChEIs [58,59]. The effect of BL on the AChE activity in the rat hippocampus caused by Sco is shown in Figure 5A.…”
Section: Effects Of Bay Leaf Incense (Bl) On Ache-inhibiting Activitymentioning
confidence: 99%
“…The pro-oxidative effects of Sco have been documented as it decreases the activity of antioxidant enzymes such as SOD, CAT, and GPX [63,64] and increased the concentration of malondialdehyde (MDA), which is the main marker of lipids peroxidation [64,65]. Also, numerous studies have shown the pro-cognitive impact of antioxidant compounds on Sco-induced memory damage, possibly by attenuating oxidative stress markers [27,58]. As demonstrated by a substantial increase in SOD and CAT specific activities and the total content of reduced GSH, along with a decrease in protein carbonyl and MDA levels, BL significantly restored the antioxidant status in the brain of rats.…”
Section: Effects Of Bay Leaf Incense (Bl) On the Hippocampus Oxidativmentioning
confidence: 99%